3D printing of functional microrobots - Li, Jinhua; Pumera, Martin (Chemical Society reviews, 2021)
3D printing (also called "additive manufacturing" or "rapid prototyping") is able to translate computer-aided and designed virtual 3D models into 3D tangible constructs/objects through a layer-by-layer deposition approach. Since its introduction, 3D printing has aroused enormous interest among researchers and engineers to understand the fabrication process and composition-structure-property correlation of printed 3D objects and unleash its great potential for application in a variety of industrial sectors. Because of its unique technological advantages, 3D printing can definitely benefit the field of microrobotics and advance the design and development of functional microrobots in a customized manner. This review aims to present a generic overview of 3D printing for functional microrobots. The most applicable 3D printing techniques, with a focus on laser-based printing, are introduced for the 3D microfabrication of microrobots. 3D-printable materials for fabricating microrobots are reviewed in detail, including photopolymers, photo-crosslinkable hydrogels, and cell-laden hydrogels. The representative applications of 3D-printed microrobots with rational designs heretofore give evidence of how these printed microrobots are being exploited in the medical, environmental, and other relevant fields. A future outlook on the 3D printing of microrobots is also provided.